THE IMPOSITION OF VALUE ADDED TAX (VAT), SALES TAX ON LUXURY GOODS (PPNBM), AND MOTOR VEHICLES TAX (PKB) ON FOUR-WHEEL VEHICLES HAS EFFECTS ON CONSUMERS' PURCHASE POWER? - Murdiansyah, Isnan -; Lestari, Yona Octiani (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
One of the biggest sources of governmental funding is taxes. One area that generates a significant amount of tax money is the car industry. Each vehicle product is subject to three different forms of taxes, including PPN, PPnBM, and PKB. These levies are put in place to control how much individuals consume. The focus of this research is to examine how the imposition of taxes on the vehicle industry affects the purchasing power of consumers of cars in Malang. This survey includes up to 100 respondents from a sample of those who purchase vehicles in 2021 and receive PPnBM price reduction. Multiple linear regression analysis is used in this study using the SPSS 25 program. Primary data collected through questionnaires is the source of data used. Based on the outcomes of multiple regression analysis, the results of this analysis show that the variables PPN (X1), PPnBM (X2), and PKB (X3) have an impact on purchasing power simultaneously (Y). PPN (X1) has a positively significant impact on purchasing power, according to results that were only partially collected. Purchase power is partially significantly positively impacted by the PPnBM variable (X2). Purchase power is partially significantly positively impacted by the PKB variable (X3). It is clear that vehicle owners receive more status and prestige in their society when higher taxes are collected.